Predictors of the age of autism spectrum disorder diagnosis: A North Carolina Cohort - Twyla Perryman; Linda R Watson; Frances Chumney (Autism and Developmental Language Impairments, 2018)
Background and aims This study investigated timing of diagnosis for African American (n = 50) and European American (n = 118) children with autism spectrum disorder in a North Carolina sample. Methods Using survey methods, a total of 168 North Carolina families were recruited. Results The two racially diverse groups did not differ significantly in the age at diagnosis of autism spectrum disorder (African American: M  = 49.72, SD  = 25.83; European American: M  = 43.78, SD  = 20.16; t (75) = 1.45, p  = .15, 95% CI [−14.10, 2.22], d  = .27; BF 10  = .582). Exploratory analyses revealed that within the African American sample, the age of diagnosis was positively correlated with parental ratings of Social Motivation from the Social Responsiveness Scale ( r  = .30, p  < 0.05). This correlation was non-significant and close to zero ( r  = −0.03, p  > 0.05) for the European American sample. Additionally, children who received another initial diagnostic label had a later age of diagnosis for autism spectrum disorder. This finding had a larger effect size in the African-American group. Conclusions The differential findings for the two groups may reflect variable interpretations of autism spectrum disorder symptoms, or a greater impact of later diagnosis on symptom severity in certain populations. Implications Our findings reflect the need for continued exploration of symptom interpretation among various racial/ethnic groups.